Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.12659/msm.907404
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Uterine Artery Embolization (UAE) versus Laparoscopic Cesarean Scar Pregnancy Debridement Surgery (LCSPDS) in Treatment of Cesarean Scar Pregnancy

Abstract: BackgroundThe present study aimed to compare the clinical efficacy and safety of uterine artery embolization (UAE) vs. laparoscopic cesarean scar pregnancy debridement surgery (LCSPDS) in the treatment of patients with cesarean scar pregnancy (CSP).Material/MethodsA retrospective analysis was performed on 87 CSP patients from March 2012 to February 2017. For the included 87 cases, 51 were treated with UAE and 36 were treated with LCSPDS. The operation success rate, intraoperative blood loss, operation time, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Non-surgical methods are based on the administration of MTX, whereas surgical treatments consist of removing the GS from the scar [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-surgical methods are based on the administration of MTX, whereas surgical treatments consist of removing the GS from the scar [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the Obstetrics and Gynecology Branch of the Chinese Medical Association published the Expert Consensus on Diagnosis and Treatment of Uterine Scar Pregnancy after Cesarean Section , which determined the role of prophylactic UAE in treatment for CSP, especially for patients with CSP II/III. 11 , 14 The exact pathogenesis of CSP remains unclear. Some studies have shown that occurrence of CSP is related to scar defects after cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to select the appropriate size of the materials used for embolization because of the potential of breaking off during the procedure, leading to ectopic embolization ( 24 ). Therefore, the embolization process should be hyper-selective, target the vessel furthest from the lesion to avoid the remaining small co-trunk vessels, and be performed slowly under fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%